Human limbal biopsy–derived stromal stem cells prevent corneal scarring - Basu, Sayan (Sci Transl Med, 2014)
Conventional allograft therapy for corneal scarring is widespread and successful, but donor tissue is not universally available, and some grafts fail owing to rejection and complications such as endothelial failure. We investigated direct treatment of corneal scarring using autologous stem cells, a therapy that, if successful, could reduce the need for corneal grafts. Mesenchymal cells were expanded from small superficial, clinically replicable limbal biopsies of human cadaveric corneo-scleral rims. Limbal biopsy–derived stromal cells (LBSCs) expanded rapidly in media containing human serum, were highly clonogenic, and could generate spheres expressing stem cell genes (ABCG2, Nestin, NGFR, Oct4, PAX6, and Sox2). Human LBSCs differentiated into keratocytes expressing characteristic marker genes (ALDH3A1, AQP1, KERA, and PTGDS) and organized a thick lamellar stroma-like tissue containing aligned collagen and keratan sulfate proteoglycans when cultured on aligned nanofiber substrata. When engrafted into mouse corneal wounds, LBSCs prevented formation of light-scattering scar tissue containing fibrotic matrix components. The presence of LBSCs induced regeneration of ablated stroma with tissue exhibiting lamellar structure and collagen organization indistinguishable from that of native tissue. Because the limbus can be easily biopsied from either eye of an affected individual and LBSCs capable of corneal stromal remodeling can be expanded under xeno-free autologous conditions, these cells present a potential for autologous stem cell–based treatment of corneal stromal blindness.